Participatory Communication to Strengthen Farmers' Empowerment and Adaptation in Facing the Impacts of Climate Change - Abdullah, Said; Sarwoprasodjo, Sarwititi; Hapsari, Dwi Retno (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Agriculture and farmers are sectors and parties affected by climate change. Unfortunately, farmers' knowledge and adaptive capacity are still low due to the limited climate change information that they receive. The development of communication models to strengthen the interaction and flow of information has been very active. However, it has not yet addressed the lack of empowerment and scarcity of farmer participation. Therefore, we need a dialogical, horizontal, participatory communication model with an emphasis on empowerment and farmer participation. This research, using a participatory communication model, aims to see how participatory communication can encourage the empowerment and adaptability of farmers to climate change. This study uses a participatory action research approach with participatory data collection techniques for the Rural Communications Assessment (PRCA). The theory used is participatory communication and social change, which allows farmers and researchers to be equally involved and dialogue to occur. This research demonstrates the fact that participatory communication through a dialogue process can promote common goals and action in dealing with climate change. In addition, this research was also able to increase farmer empowerment, which was marked by changes at the individual farmer and social levels. These changes take the form of strengthening farmers' knowledge, perceptions, and skills related to climate change and adaptation actions and increasing farmer participation in village development planning. Farmers have been able to push the issue of strengthening farmer resilience to become part of the village development plan.